EXPLORING THE LANGUAGE PRODUCTION OF SDLB STUDENTS OF SINAR HARAPAN PROBOLINGGO - Sugeng Edy Mulyono; Erwin Nur Hamsiyah (Program Studi Bahasa Inggris, Universitas Panca Marga, 2022)
The research analyzed on “Exploring the language production of SDLB students of Sinar Harapan Probolinggo”. The scope of this thesis is psycholinguistics approach and the limitation of this research focus on deaf children.The method used in this study is descriptive qualitative method. Based on the results the analysis of research data it can be concluded that deaf students generalize to objects that 5 students (Nurmala, Shita, Angga, Jilfanda and Alif). There is the research area in SDLB Sinar Harapan Probolinggo. This research show a picture and student’s mention of word to be found from the picture noun, adjective, verb and number. There are of noun (kata benda) 28 (55%) data, adjective is (kata sifat) 13 (25, 4%) data, verb (kata kerja) 6 (11, 7%) data and number (kata bilangan) 4 (7, 8%) data. The production of vocabulary the produced by deaf children to be dominated responds more quickly to the concrete than the abstract by word the deaf child on SDLB Sinar Harapan. The determination language production by deaf students of nouns reaches data that is high 55%. The deaf students are difficult to mention the word of number. The language production on five grade by deaf children least of 7,8% data in SDLB Sinar Harapan Probolinggo